A Study on the Relationship Between the Rhythm and Mathematics Skills of 5–6 year old Children - (:unkn) unknown (SAGE Publications Ltd, 2010)
This is a relational scan study aiming to question the relationship between rhythm skills which are the most fundamental element in musical development and mathematics ability. Also within the general aims of the study is to examine whether this relationship varies with respect to the personal characteristics of 5–6 year olds. It has been anticipated that children with high rhythm skills would also have high mathematics skills, and that the rhythm and mathematics skills of 5–6 year olds would vary by age and sex. The findings seem to corroborate this presupposition. The scope and content of preschool education is crucially important in child development as preschool education directly affects children's future lives. It is for this reason that preschool activities should support all areas of child development. © 2010 A B Academic Publishers Printed in Great Britain.